Removal of Integrated Hepatitis B Virus DNA Using CRISPR-Cas9 - Li, Hao; Sheng, Chunyu; Wang, Shan; Yang, Lang; Liang, Yuan; Huang, Yong; Liu, Hongbo; Li, Peng; Yang, Chaojie; Yang, Xiaoxia; Jia, Leili; Xie, Jing; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
The presence of hepatitis B virus (HBV) covalently closed circular DNA (cccDNA) and the permanent integration of HBV DNA into the host genome confers the risk of viral reactivation and hepatocellular carcinoma. Nucleoside/nucleotide analogs alone have little or no capacity to eliminate replicative HBV templates consisting of cccDNA or integrated HBV DNA. Recently, CRISPR/Cas9 technology has been widely applied as a promising genome-editing tool, and HBV-specific CRISPR-Cas9 systems were shown to effectively mediate HBV cccDNA disruption. However, the integrated HBV DNA fragments are considered as important pro-oncogenic properties and it serves as an important template for viral replication and expression in stable HBV cell line. In this study, we completely excised a full-length 3,175-bp integrated HBV DNA fragment and disrupted HBV cccDNA in a stable HBV cell line. In HBV-excised cell line, the HBV cccDNA inside cells, supernatant HBV DNA, HBsAg, and HBeAg remained below the negative critical values for more than 10 months. Besides, by whole genome sequencing, we analyzed off-target effects and excluded cell contamination. It is the first time that the HBV infection has been fully eradicated in a stable HBV cell line. These findings demonstrate that the CRISPR-Cas9 system is a potentially powerful tool capable of promoting a radical or “sterile” HBV cure.